The effect of high-load vs. high-repetition training on endurance performance - Ebben, W. P.; Kindler, A. G.; Chirdon, K. A.; Jenkins, N. C.; Polichnowski, A. J.; Ng, A. V. (The Journal of Strength and Conditioning Research, 2004)
The purpose of this study was to compare the effects of high-load (H-load) periodized resistance training and high-repetition (H-rep) reverse step loading periodized resistance training on endurance performance. Twenty-six female university rowers (age = 20 ± 1 year) were randomly assigned to H-load (5 novice, 8 varsity) or H-rep (7 novice, 6 varsity) groups. Subjects were pre- and posttested using a 2,000-m rowing ergometer test. Outcome variables included O2 peak, time to test completion, total power, average power per stroke, total number of strokes, stroke rate, and body mass. Subjects trained for 8 weeks using identical exercises. Varsity rowers who performed H-load training demonstrated greater improvement compared with those who performed H-rep training. Novice rowers who performed H-rep training demonstrated greater improvement compared with those who performed H-load training. High-load periodized training appears to be more effective for athletes with advanced training status, and H-rep reverse step loading periodized training is more effective for those who are relatively untrained.